+0  
 
0
50
1
avatar+560 

Let f(y) = y^4 -3y^3 +y - 3 and g(y) = y^3 + 7y^2 -2. Find $f(y) + g(y)$. Write your answer as a polynomial with terms of decreasing degree.

Lightning  Jul 24, 2018
 #1
avatar+19813 
+1

Let f(y) = y^4 -3y^3 +y - 3 and g(y) = y^3 + 7y^2 -2. Find $f(y) + g(y)$.

Write your answer as a polynomial with terms of decreasing degree.

 

\(\begin{array}{|rcrcrcrcrcr|} \hline f(y) &=& y^4 &-& 3y^3 & & &+& y &-& 3 \\ g(y) &=& & & y^3 &+& 7y^2 & & &-& 2 \\ \hline f(y)+g(y) &=& y^4 &-& 2y^3 &+& 7y^2 &+& y &-& 5 \\ \hline \end{array}\)

 

laugh

heureka  Jul 25, 2018

17 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.